Resolving Non-Performing Financing in MSMEs by Islamic Banking: Study from PT. Bank Syariah Indonesia Tbk - Manggala Putri, Syah Amelia; Eka Jati Rahayu Firmansyah; Tria Isti Wulandari (Universitas Ahmad Dahlan, 2023)
Abstract Introduction to The Problem: MSMEs have proven resilient to various crises and significantly contribute to the national economy. The primary support is financing for both investment and working capital. However, MSME financing is seen as having a high risk by banks, which is feared will result in losses. Islamic banks must have an exit strategy in dealing with NPF so that the distribution of MSME financing can grow healthily and sustainably. Purpose/Objective Study: The paper aims to analyze how Islamic banks resolve non-performing financing disbursed to MSMEs. Design/Methodology/Approach: We used a qualitative method with a field research approach. The research was a case study examining primary data collected through observation, interviews, and documentation. The validation test used a triangulation method by comparing the interview results and the research subjects. Findings: Islamic banks resolved non-performing financing in MSMEs through non-performing financing warning, rescuing, and resolving. They conferred warnings by billing to collect customers’’ funds serving as payment for overdue liabilities. As regards rescuing non-performing financing, rescheduling, reconditioning, and restructuring were conducted. Finally, they resolved non-performing financing through novation, compensation, collateral liquidation, and court settlement Paper Type: Research Article